The Aktivitas Literasi Terhadap Sikap Belajar Anak Usia Sekolah - Sinulingga, Elysabeth; Ompusunggu, Fransiska; Delima Hutapea, Adventina; Cathryne, Joice; Kartika, Lia; Nova, Fiorentina (Jurnal Pustaka Keperawatan (Pusat Akses kajian Keperawatan), 2025)
Instilling a culture of literacy in today's digital era begins with children's interest in learning. One of them is through reading and writing literacy. However, rapidly developing technological capabilities and an increasingly sophisticated era create new problems for children due to low interest in literacy. The low level of literacy in children is an alarm in the development of human resources to determine the future of the nation, so this is the background for conducting education related to children's literacy activities on the learning attitudes of school-age children. The form of education is carried out through hybrid community service (PkM) through Zoom and at the locations of TBA Arumba 91 and Yayasan SD Masehi GBKP Kabanjahe, North Sumatra, with participants being elementary school students consisting of grades 4-6 SD. The implementation method is pre-test, post-test, material presentation, and discussion. The topic explained at this seminar is education about literacy activities that can be done in schoolchildren, especially health literacy and healthy living education in school-age children. This activity was attended by 127 participants, and all of them participated from the beginning to the end of the activity. The results of the activity obtained an increase in understanding from the participants based on the average value of the pre-test (before given the material = 62.70) and post-test (after given the material = 74.20) with a p-value = 0.001. Literacy activities enhance children’s interest, concentration, and critical thinking; parents and teachers should regularly involve them in enjoyable literacy activities.